Background levels of zinc, iron, manganese and copper in soil series of Haryana and their relationship with soil properties - MALIK, R S; YADAV, H K; NARENDER, NARENDER; RAJPAUL, RAJPAUL; SANGWAN, P S (The Indian Journal of Agricultural Sciences, 2017)
The availability of micronutrients under Aeolian plain, alluvial plain and Aravali hills soils of Haryana may be influenced due to different agro-climatic features and also variation in physico-chemical properties of the soil, which may ultimately affect the optimum crop yield. The soils are neutral to alkaline in reaction, safe in electrical conductivity, low to high in organic carbon content and slightly calcareous in nature. According to the concept of soil nutrient index soils are deficient in DTPA-Zn while sufficient in DTPA-Mn, Fe and Cu content which underlines the need of Zn application in order to enhancing the crop productivity. Thus, it is clear from the investigation that available Zn, Cu, Fe and Mn concentration in soil of different districts in various soil series varied considerably in alluvial zone of Haryana. Organic carbon content in soil was found positively and significantly correlated with DTPA extractable Zn, Cu and Fe. Soil pH did not show any relationship with available Zn, Cu, Fe and Mn in all the soils falls under different series.